Say Anarcha : a young woman, a devious surgeon, and the harrowing birth of modern women's health - Hallman, J. C. (Henry Holt and Company, 2023)
"In 1846, a young surgeon, J. Marion Sims ("The Father of Gynecology"), began several years of experimental surgeries on a young enslaved woman known as Anarcha ("The Mother of Gynecology"). This series of procedures--performed without anesthesia and resulting in Anarcha's so-called "cure"--Forever altered the path of women's health. Despite brutal practices and failed techniques, Sims proclaimed himself the curer of obstetric fistula, a horrific condition that had stymied the medical world for centuries. Parlaying supposed success to the founding of a new hospital in New York City--where he conducted additional dangerous experiments on Irish women--Sims went on to a profitable career treating gentry and royalty in Europe, becoming one of the world's first celebrity surgeons. Medical text after medical text hailed Anarcha as a pivotal figure in the history of medicine, but little was recorded about the woman herself. Through extensive research, author J.C. Hallman has unearthed the first evidence ever found of Anarcha's life that did not come from Sims's suspect reports. With incredible tenacity, Hallman traced Anarcha's path from her beginnings on a Southern plantation to the backyard clinic where she was subjected to scores of painful surgical experiments, to her years after in Richmond and New York City, and to her final resting place in a lonely Virginia forest. When Hallman first set out to find Anarcha, the world was just beginning to grapple with the history of white supremacy and its connection to racial health disparities exposed by COVID-19 and the disproportionate number of Black women who die while giving birth. In telling the stories of the "Mother" and "Father" of gynecology, Say Anarcha excavates the history of a heroic enslaved woman and deconstructs the biographical smokescreen of a surgeon whom history has falsely enshrined as a heroic pioneer. Kin in spirit to The Immortal Life of Henrietta Lacks, Hallman's dual biographical narratives tell a single story that corrects errors calcified in history and illuminates the sacrifice of a young woman who changed the world only to be forgotten by it--until now"--